Discovering Tutankhamun - Collins, P; McNamara, L (Ashmolean Museum, 2014)
This book tells the story of the search for Tutankhamun's tomb and its discovery using Howard Carter's original excavation records that were deposited in the archives of the Griffith Institute at the University of Oxford.